Implikasi Pengalaman Etnomatematika dan Gender Terhadap Pemahaman Konsep Bilangan Siswa - Tandri Patih; Halistin Halistin; Rahma Okta Saputri; Azia Azia (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
This research is causal-quantitative research that aims to find out and examine the implications/influence of ethnomathematical experiences, namely things that have been experienced by students related to mathematics who was born based on the culture and value system of an ethnic group; and differences in characteristics on the understanding of the students’ number concept. is a trait used as the basis for identifying differences between men and women in terms of socio-cultural conditions, values ​​and behavior, mentality, and so on. The research was carried out in the even semester of the 2020/2021 academic year at SMP Negeri 3 Kendari. The results show that the experience of ethnomathematics has a significant effect on understanding the concept of numbers by 0.302. Meanwhile, differences in characteristics have no effect on students' understanding of the concept of numbers at SMP Negeri 3 Kendari. This result explains that if students' ethnomathematical experience increases by one unit, then students' knowledge of mathematical concepts will increase by 0.302 units. Ethnomathematics experience can be used to design mathematics learning in an ethnomathematical context based on local wisdom in the classroom. Teachers can consider using ethnomathematical contexts based on students' experiences with traditional games they know and have played to create a condition for learning mathematics that is fun and easier to understand because it is close to students' daily lives and contains cultural values ​​that can shape students' character.